Ethanol Disrupts the Protective Crosstalk Between Macrophages and HBV-Infected Hepatocytes - Murali Ganesan; Anup S. Pathania; Grace Bybee; Kusum K. Kharbanda; Larisa Y. Poluektova; Natalia A. Osna (Biomolecules)
About 296 million people worldwide are living with chronic hepatitis B viral (HBV) infection, and outcomes to end-stage liver diseases are potentiated by alcohol. HBV replicates in hepatocytes, but other liver non-parenchymal cells can sense the virus. In this study, we aimed to investigate the regulatory effects of macrophages on HBV marker and interferon-stimulated genes (ISGs) expressions in hepatocytes. This study was performed on HBV-replicating HepG2.2.15 cells and human monocyte-derived macrophages (MDMs). We found that exposure of HepG2.2.15 cells to an acetaldehyde-generating system (AGS) increased HBV RNA, HBV DNA, and cccDNA expressions and suppressed the activation of ISGs, APOBEC3G, ISG15, and OAS1. Supernatants collected from IFNα-activated MDMs decreased HBV marker levels and induced ISG activation in AGS-treated and untreated HepG2.215 cells. These effects were reversed by exposure of MDMs to ethanol and mimicked by treatment with exosome release inhibitor GW4869. We conclude that exosome-mediated crosstalk between IFN-activated macrophages and HBV-replicating hepatocytes plays a protective role via the up-regulation of ISGs and suppression of HBV replication. However, ethanol exposure to macrophages breaks this protection.